The Relationship Between Career Maturity and Quarter-Life Crisis Among Final-Year Students at UIN Ar-Raniry Banda Aceh - Ananda, Teuku Wanza Agha; Jannah, Miftahul; Nova, Vera; Nasruddin, Nasruddin (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The quarter-life crisis is a period of turmoil in which individuals experience anxiety and restlessness as they begin to question their life goals, direction, achievements, and overall life satisfaction. Based on field observations, many final-year students experience this phenomenon, including students at UIN Ar-Raniry Banda Aceh. This may occur because final-year students are in a transitional phase from the academic world to the professional world, leading them to begin questioning their future careers. The purpose of this study was to determine the relationship between career maturity and quarter-life crisis among final-year students at UIN Ar-Raniry Banda Aceh. This research employed a quantitative approach with a correlational method. The sampling technique used was quota sampling. The population in this study consisted of 4,913 final-year students, with a sample of 239 students. The instruments used were the Career Maturity Scale, developed based on the aspects proposed by Super (as cited in Saifuddin, 2018), and the Quarter-Life Crisis Scale, constructed based on the aspects proposed by Robbins and Wilner (2001). The hypothesis testing technique used was the Pearson Product-Moment correlation analysis, which produced a correlation coefficient of r = -0.544 with a significance value of p = 0.000. These results indicate a significant negative relationship between career maturity and quarter-life crisis, meaning that the higher the career maturity, the lower the quarter-life crisis experienced by final-year students at UIN Ar-Raniry Banda Aceh.